Standardisation of Gharr-1 Gamma Spectroscopy System for Instrumental Neutron Activation Analysis (Journal of Science and Technology, 2016)
The gamma-ray spectroscopy system at the Ghana Atomic Energy Commission Research Reactor (GHARR-1) Centre has been standardized with 5 standard reference materials, 6 pure elements and 5 chemically pure compounds for Instrumental Neutron Activation Analysis (INAA) using the Absolute Method. The results from the validation of the standardization procedure using an NBS SRM 1663a Coal Fly Ash compared very well with the certified values.